fra Din Misbruger / from You/r Addict - Skinnebach, Lars (Nordlit, 2007)
An extract from You/r Addict (2006), discussed in the article "How often can you ask your reader to leave?" Text and Reader in Lars Skinnebach: Din misbruger (You/r addict). by Marianne Ølholm